Crescimento e produtividade do algodoeiro em função da aplicação de subdoses de 2,4-d e cloreto de mepiquat - Américo, Gabriela Helena Pinê [UNESP] (2015)
Due to expansion of cotton production, research with growth regulators and sublethal rates of herbicide are being developed to improve levels of crop productivity. The aim of this study was to evaluate the effect of sublethal rates of dichlorophenoxyacetic acid and mepiquat chloride on vegetative and productive characteristics of two cultivar of cotton plant. The experiment was conducted during the growing season of 2012/2013 and 2013/2014. The experimental design was a randomized completely blocks design in a factorial system 6 x 2 x 2 with 4 replications, consisting 96 plots, with the amount of twenty four treatments: one control and five rates of 2,4-D: 0.68, 1.36, 2.04 2.72 and 3.40 g equivalent acid (e.a) by ha -1, with and without application of mepiquat chloride in the level 200 mL ha-1 in the cultivar FMT 701 and Fibermax 966 cotton. Applied to the doses of 2,4-D at 45 days after plant emergence (d.a.e.) and the growth regulator to 70 d.a.e. The result showed that the use of the growth regulator (mepiquat chloride) at a dose 200 mL ha -1 was effective in controlling plant development in relation to plant height on the two-year study. For the small size of cultivar, the application of increasing doses of 2,4-D provides an increase in plant height. With increasing doses of 2,4-D, there is an increase in the number of reproductive structures for cultivating FMT 701. The application doses of 2,4-D in the range of 1.75 and 1.90 g. The. ha - 1 provides an increase of seed cotton productivity to grow FMT 701. To cultivate Fibermax 966 to sub-dose of 1.75 provides an increase in cotton productivity in seed. Cultivar FMT 701 obtained the highest plant height, stem diameter, number of reproductive branches, bolls per plant and cotton productivity in seed compared with the cultivar Fibermax 966 in both years